CĂRŢILE ELECTRONICE – CONTEXT ŞI DILEME - HARJEVSCHI, director general, Biblioteca Municipală „B.P. Hasdeu”, Mariana (BIBLIOPOLIS, 2020)
The article explores a number of issues on ebook lending models applied in different countries. It also discusses the efforts of librarians in finding solutions for delivering ebooks for its users. The author cites different research resources and international guidelines to get a better picture of the situation on the market of ebook development and delivery.